« Le Crépuscule de la chevalerie » : le cycle arthurien de Rutland Boughton (1878-1960) et l’épopée nationale - Nadège Le Lan (Revue LISA)
“A man holding in one hand a crown of laurel, in the other a crown of thorn”. This is the closing vision of the first part of Rutland Boughton’s Arthurian cycle, composed between 1908 and 1945 (The Round Table, 1915; The Birth of Arthur, 1920; The Lily Maid, 1934; Galahad and Avalon, never produced). The work advocates communal principles with a Christian spirit and the union of human beings with nature. It intends to imitate Wagner’s Ring and faces the double goal of being national and modern. The study focuses on the libretto, through both the adaptation of the national myth and the reference to Wagner.